TADWIN HADIS DAN KONTRIBUSINYA DALAM PERKEMBANGAN HISTORIOGRAFI ISLAM - saifuddin, saifuddin (Jurnal Ilmu Ushuluddin, 2010)
Historically, the process of tadwîn was through by the phases of a long and complex historical and colored many controversies. The controversy intensified when considering stream factor in it. Three traditional currents in Islam, Ahl al - Sunnah wa al - Jamaah, Shiites, and Kharijites, proved to have a history of their own tadwîn traditions were different from each other. Concurrently with the tadwîn process of hadith, the scholars also put its methodological tools. Methodological tools that in turn give effect to other disciplines, including Islamic historiography. This study tried to discover more about the dynamics that occured in the tadwîn tradition process and to what extent it impacted to the Islamic historiography. Through the method of historical - comparative historical or combined with Usul al - hadîts, this study revealead that the hadith tadwîn basically been going on since the period of the Prophet and continued in subsequent periods until finally composed " Six Major Hadith Compilation " among the Ahl al - Sunnah wa al - Jamaah and the " Four Major Hadith Compilation " ( al -Kutub al - Arbaah ) among Shiites. The study also showed that tadwîn of hadith clearly had a contribution which was not only limited to providing abundant material for writing the history of Islam in the form of biography (sirah) and military raids or attacks (maghâziy), but more importantly also about resource gathering methods, method of source criticism, and methods of preparation work of Islamic history .